Gender differences in the price elasticity of demand for waterpipe and cigarette smoking in Lebanon, Jordan and Palestine: a volumetric choice experiment. Issue 7 (18th July 2022) - Awawda, Sameera; Chalak, Ali; Khader, Yousef; Mostafa, Aya; Abla, Ruba; Nakkash, Rima; Jawad, Mohammed; Salloum, Ramzi G; Abu-Rmeileh, Niveen ME
Abstract : Objectives: This study assessed the extent to which the elasticity of cigarette and waterpipe tobacco products differs between men and women. We also explored the levels of substitution and complementarity in tobacco products among men and women. Setting: The study examines tobacco elasticities in three Arab countries: Lebanon, Jordan and the West Bank of Palestine. Participants: We used data from nationally representative surveys of adults aged ≥18 years in Lebanon (n=1680), Jordan (n=1925) and Palestine (n=1679). The proportion of women was 50.0% of the sample in Lebanon and Palestine, and 44.6% in Jordan. Primary and secondary outcome measures: A zero-inflated Poisson regression model estimated own-price and cross-price elasticities for two variations of cigarettes and five variations of waterpipe tobacco products. Elasticities were measured based on eight scenarios of prices. Results: Demand for waterpipe tobacco products was elastic for both men and women. The cross-price elasticities in the three countries indicate the existence of substitution between cigarettes and waterpipe products and by different varieties within each of the two tobacco products. Gender differences varied across the three countries whereby higher cross-price elasticities were observed for women in Jordan and Palestine. For example, the price elasticity for discount waterpipe was −1.4 and −0.6 for women and men in Jordan, respectively. Conclusions: Results on the elasticity of demand for tobacco products and the existence of substitution between tobacco products reveal the higher responsiveness of men and women to changes in tobacco prices. This should be taken into consideration in tobacco control strategies particularly when reducing tobacco consumption via taxation policies.